Influence of Seaweed (Padina antrillarum) Extract Foliar Application on Growth and Flowering of Roses Variety ‘Local’ - Kularathne, M.A.M.N.; Srikrishnah, S.; Sutharsan, S. (International Journal of Applied Sciences and Biotechnology, 2021)
The Seaweed (Padina antrillarum) abundantly found in the coastal region of Eastern Sri Lanka. Seaweed contains a wide range of nutrients and hormones for plant growth. An experiment was conducted at the Crop Farm, Eastern University, Sri Lanka to assess the effects of seaweed (Padina antrillarum) extract on the flowering of roses var. ‘Local’ from July to September 2020. Four treatments were used in this experiment viz. 10% (T1), 20% (T2), and 30% (T3) seaweed extracts with control treatment (T4). Treatments were applied at once-a-week interval. The experimental design was a completely randomized design with three replications. All other management practices were followed uniformly. Measurements were done at once a month. Collected data were analyzed. The higher performances in measured parameters (plant height, leaf area, plant biomass, number of flowers per plant) were observed in T2. It showed that once a week application of 20% seaweed liquid extract had the potential to increase growth and flower production in roses. It might be due to the presence of nutrients and the growth hormones in seaweed extract and optimum concentration of seaweed extract received by plants at T2. In T1 and T3, plants received sub-optimum and higher concentration respectively. It could be the reason for the lowest performances in these treatments. From this experiment, it could be concluded that once a week application of 20% seaweed liquid extract of Padina antrillarum is suitable to increase flowering in roses of treatment tested.